Understanding Generation Z’s Intention to Use Digital Banks: The Role of Perceived Usefulness and Attitude - Putri, Nyayu Khalilah; Sulastri, Sulastri; Adam, Mohamad; Yuliani, Yuliani (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The rapid growth of digital banking services has transformed the financial industry, particularly in attracting younger consumers who are highly dependent on technology. However, understanding the behavioral factors that influence digital banking adoption remains a critical challenge for financial institutions. This study aims to analyze the determinants of Generation Z’s intention to use digital banking services by applying the Technology Acceptance Model, with a particular focus on the mediating role of attitude. Using a quantitative research design, data were collected from 100 Generation Z respondents through purposive sampling. The study examines the relationships among perceived usefulness, attitude, and intention to use digital banking. The results indicate that perceived usefulness has a positive and significant effect on both attitude and intention to use, while attitude significantly mediates the relationship between perceived usefulness and usage intention. The findings demonstrate that users’ perceptions of functional benefits, efficiency, and convenience play a crucial role in shaping favorable attitudes and strengthening adoption behavior. This study highlights the importance of integrating technological value and user-centered design in digital banking services. By providing empirical evidence on Generation Z’s technology acceptance behavior, this research contributes to the literature on digital finance and offers practical implications for banks in developing effective digital strategies to enhance customer engagement and long-term adoption.